2022
DOI: 10.1186/s12876-022-02266-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of six endoscopy independent scoring systems for the prediction of clinical outcomes for elderly and younger patients with upper gastrointestinal bleeding

Abstract: Objectives To compare the predictive ability of six pre-endoscopic scoring systems (ABC, AIMS65, GBS, MAP(ASH), pRS, and T-score) for outcomes of upper gastrointestinal bleeding (UGIB) in elderly and younger patients. Methods A retrospective study of 1260 patients, including 530 elderly patients (age $$\ge$$ ≥ 65) and 730 younger patients (age < 65) presenting with UGIB, was performed at Zhongda Hospital So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…GBS and RS are complex and sometimes difficult to use in emergency settings due to their low accuracy. Thus, during the last 10 years, other scores have been proposed for predicting intervention, including the N-score [ 8 ], Iino score [ 7 , 9 ], and H3B2 [ 7 ], or for predicting mortality, such as the MAP score [ 10 , 11 ], INBS (International Bleeding Score), PNED (Progetto Nazionale Emmoragia Digestive) [ 12 ], and Harbinger score [ 13 ]. H3B2 was proposed in 2019 and is useful for the prediction of therapeutic interventions, including emergency endoscopy, with an accuracy superior to both GBS and modified GBS, and also with satisfactory accuracy in mortality prediction [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…GBS and RS are complex and sometimes difficult to use in emergency settings due to their low accuracy. Thus, during the last 10 years, other scores have been proposed for predicting intervention, including the N-score [ 8 ], Iino score [ 7 , 9 ], and H3B2 [ 7 ], or for predicting mortality, such as the MAP score [ 10 , 11 ], INBS (International Bleeding Score), PNED (Progetto Nazionale Emmoragia Digestive) [ 12 ], and Harbinger score [ 13 ]. H3B2 was proposed in 2019 and is useful for the prediction of therapeutic interventions, including emergency endoscopy, with an accuracy superior to both GBS and modified GBS, and also with satisfactory accuracy in mortality prediction [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Iino or Hirosaki score was proposed in 2016 for predicting intervention in a study of 212 patients in Japan and demonstrated superiority to both clinical Rockall and AIM65 [ 14 ]. MAP score was proposed in 2020 for the prediction of both intervention and risk of death [ 10 ], and INBS (ABC score) was proposed in an international cohort study in order to better assess mortality risk [ 15 ] and subsequently validated in other studies as superior to preclinical Rockall, GBS, PNED and AIM65 [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation